Mauro Fernández acuña y el humanismo en Costa Rica - Saxe Fernández, Eduardo E. (2010)
In this article I first criticize the Christian and capitalist notion of “humanism”, and then I present a possible, more positive but provisional interpretation of this concept, understanding it as a “struggle against” dogmatisms and superstitions. Then I consider Mauro Fernández Acuña ́s accomplishments and defend him from the false accusations presented mostly by Costa Rican Catholic groups and ideologues.